Regulation of HTLV-1 Gag budding by Vps4A, Vps4B, and AIP1/Alix - Urata, Shuzo (BioMed Central, 2007)
BACKGROUND: HTLV-1 Gag protein is a matrix protein that contains the PTAP and PPPY sequences as L-domain motifs and which can be released from mammalian cells in the form of virus-like particles (VLPs). The cellular factors Tsg101 and Nedd4.1 interact with PTAP and PPPY, respectively, within the HTLV-1 Gag polyprotein. Tsg101 forms a complex with Vps28 and Vps37 (ESCRT-I complex) and plays an important role in the class E Vps pathway, which mediates protein sorting and invagination of vesicles into multivesicular bodies. Nedd4.1 is an E3 ubiquitin ligase that binds to the PPPY motif through its WW motif, but its function is still unknown. In the present study, to investigate the mechanism of HTLV-1 budding in detail, we analyzed HTLV-1 budding using dominant negative (DN) forms of the class E proteins. RESULTS: Here, we report that DN forms of Vps4A, Vps4B, and AIP1 inhibit HTLV-1 budding. CONCLUSION: These findings suggest that HTLV-1 budding utilizes the MVB pathway and that these class E proteins may be targets for prevention of mother-to-infant vertical transmission of the virus.